Cycle analysis and economic evaluation for seawater-LNG Organic Rankine Cycles. (1st November 2021) - Lee, Su Won; Kwon, Jin Gyu; Kim, Moo Hwan; Jo, HangJin
Abstract: An Organic Rankine Cycle (ORC) has a variety of environmental and operating conditions, which result in different efficiency and net work of cycle. In this regard, it is important to determine the optimal operating conditions with the consideration of various operating variables since the outcomes of the low-grade waste heat recovery systems are low as well as highly dependent on the conditions. In this study, the ORC having seawater as a heat source and LNG cold energy as a heat sink is analyzed with cycle parameters as well as the environmental conditions such as seawater temperature. An ORC Economic evaluation Code (OEC) is developed to consider the effects of numerous parameters such as the pump outlet pressure, mass flow rate, pinch point, materials of the heat exchangers, the type of working fluid, cycle configuration, and seawater temperature simultaneously. Based on the analysis, an economic assessment is conducted, so we could find the optimal conditions for the designed ORC systems. Also, it is found that the seawater temperature variation could affect about 23.8% in terms of net work compared to fixed heat source temperature conditions. Highlights: Economic assessment of ORC is conducted to take all selected variables into account. Sensitivity analysis is conducted according to the variables. A comparative analysis of cycles is performed according to the characteristics of working fluids. Optimal operating conditions are derived by considering changes in the seawater temperature.